(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the current situation of using simulation methods and evaluation of lecturers in nursing practical teaching at Vinh Medical University 2023. Research method: Descriptive research conducted on 28 teachers participating in training nursing students at Vinh Medical University from May to November 2023 by interviewing through the questionnaire tool. Results: Teachers often use the simulation method with a fixed structure, simulation based on anatomical models accounts for a high rate of 42.9%, 39.3% respectively. The teaching time of 1 case of practice at campus long over 180 minutes, accounting for the highest rate of 25%, and the time of teaching 1 case of practice at a practice facility long from 46 to 90 minutes, accounting for the highest rate of 25%. The level of interest and very interest in the simulation method are both very high (> 85%). The percentage of teachers who regularly apply “Assessment of attitude communication skills” is 62.3% and “Evaluate by pure recall theory questions” is 46.4%. Teachers are interested in student assessment methods at over 75%, of which the highest is “Evaluating thinking using hypothetical situations” accounting for 78.6%. Conclusion: Teachers often use simulation method with fixed structure, simulation based on anatomical model. Teachers are interested in simulation methods with fixed structures, simulation based on anatomical models, computer-based simulation, virtual patient-based simulation, real patients simulation, simulation using standard patients. Teachers are interested in student assessment methods, the highest of which is “Evaluating thinking using hypothetical situations”.